A Phase 1 Randomized, Double‐Blind, Placebo‐Controlled Trial to Assess the Safety, Tolerability, and Pharmacokinetics of a Respiratory Syncytial Virus Neutralizing Monoclonal Antibody MK‐1654 in Healthy Adults - Aliprantis, Antonios O.; Wolford, Dennis; Caro, Luzelena; Maas, Brian M.; Ma, Hua; Montgomery, Diana L.; Sterling, Laura M.; Hunt, Allen; Cox, Kara S.; Vora, Kalpit A.; Roadcap, Brad A.; Railkar, Radha A.; et al. (Clinical pharmacology in drug development, 2021)
Respiratory syncytial virus (RSV) is the leading cause of acute lower respiratory tract infection and related morbidity and mortality in infants. Passive immunization with an RSV‐neutralizing antibody can provide rapid protection to this vulnerable population. Proof‐of‐concept for this approach has been demonstrated by palivizumab; however, the use of this antibody is generally restricted to the highest‐risk infants due to monthly dosing requirements and its cost. To address the large unmet medical need for most infants, we are evaluating MK‐1654, a fully human RSV‐neutralizing antibody with half‐life extending mutations targeting site IV of the fusion protein. In this 2‐part, placebo‐controlled, double‐blind, first‐in‐human study, 152 healthy adults were randomized 3:1 to receive a single dose of MK‐1654 or placebo in 5 cohorts (100 or 300 mg as an intramuscular dose or 300, 1000, or 3000 mg as an intravenous dose). Safety, pharmacokinetics, antidrug antibodies, and RSV serum‐neutralizing antibody titers were evaluated through 1 year. MK‐1654 serum concentrations increased proportionally with dose and resulted in corresponding elevations in RSV serum‐neutralizing antibody titers. The antibody displayed a half‐life of 73 to 88 days and an estimated bioavailability of 69% at the 300‐mg dose. The overall safety profile of MK‐1654 was similar to placebo, and treatment‐emergent antidrug antibodies were low (2.6%) with no associated adverse events. These data support the continued development of MK‐1654 for the prevention of RSV disease in infants.